The Impact Of Financial Literacy And Behavioral Bias On Investment Decisions - Anggraeni, Dewi (Jurnal Ilmiah Akuntansi Manajemen, 2024)
This study aims to find out and to prove empirically the challenges of Financial Literacy, Overconfidence and Risk Perception to Investment Decisions. The sample in this study was workers in Makassar City, South Sulawesi, Indonesia. There were 135 respondents taken using questionnaires through the survey method. The statistical analysis used in this study is multiple multiple regression through the Statistical Program for Social Science (SPSS). This model was evaluated using the R-square for the dependent variable as well as the T-test and the significance of the parameter coefficients on the structural path. The results found that Financial Literacy has a Significant Positive effect on investment decisions, Overconfidence has a Significant Positive effect on investment decisions and herding behaviour positive a significant effect on investment decision-making. on investment decision-making. The development of the results also found that the tendency of respondents prefers to invest in the form of Riil Assets. furthermore, the researchers gave the result that there was no difference in financial literacy between the male and female sexes. There is no difference in overconfidence between the sexes of men and women and found differences in behaviour between the sexes of men and women but there is no difference in the decision to involve the sexes of men and women